Glimpses of Medical technology Students: The Realities of ServiceLearning - Cubelo, Teodora A. (Silliman Journal, 2022)
This study sought to determine the effects of service-learning among students enrolled in Community and Public Health. Employing content analysis, reflections of students from 2009 to 2013 were analyzed by looking at their journal entries during their community immersion. Learning experiences were grouped according to similarities, but unique recording of reflections written by a few were also included and analyzed. Reflections of the majority of students were full of positive outlook at the start of their encounter with the community, looked at their task with excitement and had willingness in their hearts to serve. Their reflections were about the joys of serving and an appreciation of whatever little they had as an individual and as a family. They realized that they had no reason to be discontented with what they had in life because they saw with their very eyes how families in the community lived with almost nothing at all. A number expressed ambivalence helping others because they too felt that they had unmet needs. In this group, a few admitted that their attitude towards the community members was wrong, and they hoped that if given another opportunity to serve, they would be kinder and less judgmental. However, the rest of those who entered the community with ambivalence indicated a change in their attitude towards the families they were serving.